Does closer placement of cerclage wire enhance functional outcomes in tension band wiring of patellar fractures? - Gökçeoğlu Yaşar Samet; Karalar Şahin; Yaptı Metin; Levent Ali (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. Patellar fractures are commonly treated with tension band wiring (TBW). The distance between the cerclage wire and the superior pole of the patella is crucial for surgical outcomes. This study evaluates the impact of this distance on clinical and functional results. Methods. A retrospective cohort study of 64 patients with transverse patellar fractures treated with TBW was conducted. Patients were categorized based on the distance of the cerclage wire from the bone: < 4 mm, 4–8.5 mm, and > 8.5 mm. Clinical outcomes included bone union, implant failure, and wound complications. Functional outcomes were assessed using range of motion (ROM) and modified Hospital for Special Surgery (HSS) knee score values. Results. Significant differences were observed in outcomes depending on wire placement. Patients with cerclage wires < 4 mm from the bone exhibited poorer functional results, with a mean modified HSS Knee Score of 70 ± 9.2 and an average ROM of 103.6 ± 42.4°. Patients with wires positioned 4–8.5 mm from the bone demonstrated better functional recovery, achieving higher knee scores and greater ROM. Statistical analysis confirmed that closer wire placement negatively affected clinical outcomes (p < 0.05). Conclusion. This study suggests that positioning cerclage wires too close to the bone (< 4 mm) may impair functional outcomes despite presumed mechanical stability. An optimal distance of 4–8.5 mm balances mechanical stability and soft tissue protection, offering improved clinical and functional results. These findings challenge conventional surgical approaches, emphasizing the importance of precise wire positioning in TBW procedures.